Exceptions to de Saussure’s Law in Kuršaitis’ Lithuanian dictionaries - Strockis, Mindaugas (Baltistica, 2021)
Analysis of the German-Lithuanian and Lithuanian-German dictionaries by Fridrikis Kuršaitis (in German known as Friedrich Kurschat) reveals that in a certain group of words of the -a declension, de Saussure’s Law fails to operate in the nominative singular, contrary to what is described (or prescribed) in modern manuals of Lithuanian accentuation. In his Lithuanian Grammar, Kuršaitis himself assigned these words to the accentuation class Ib (in modern terminology, it is a variant of accentuation class 2 applied to the -ė declension). The words in this group fall into several categories: those with the ending -ia or -ja, especially with the suffix -ija, such as lapìja ‘foliage’ or Prūsìja (‘Prussia’); feminine members of the substantiva mobilia pairs, such as garbanuõčia (‘curly-haired’); babble-words (Lallwörter) such as mãma (‘mama’); certain loanwords, such as lãva (‘lava’); as well as some other words. Similar phenomena can be observed not only in Lithuanian as it was spoken in Lithuania Minor and described by Kuršaitis, but also in modern Lithuanian dialects. This calls for a more thorough review of possible exceptions to de Saussure’s Law in Lithuanian.